Maharashtra State BoardHSC Science (Electronics) 11th
Advertisement Remove all ads

If A = [-121-32-3] and B = [21-32-13], prove that (A + BT)T = AT + B - Mathematics and Statistics

Sum

If A = `[(-1, 2, 1),(-3, 2, -3)]` and B = `[(2, 1),(-3, 2),(-1, 3)]`, prove that (A + BT)T = AT + B

Advertisement Remove all ads

Solution

A = `[(-1, 2, 1),(-3, 2, -3)]` and B = `[(2, 1),(-3, 2),(-1, 3)]`

∴ AT = `[(-1, -3),(2, 2),(1, -3)]` and BT = `[(2, -3, -1),(1, 2, 3)]`

∴ A + BT = `[(-1, 2, 1),(-3, 2, -3)] + [(2, -3, -1),(1, 2, 3)]`

= `[(-1 + 2, 2 - 3, 1 - 1),(-3 + 1, 2 + 2, -3 + 3)]`

= `[(1, -1, 0),(-2, 4, 0)]`

∴ (A + BT)T = `[(1, -2),(-1, 4),(0, 0)]`   ...(i)

Now, AT + B = `[(-1, -3),(2, 2),(1, -3)] + [(2, 1),(-3, 2),(-1, 3)]`

= `[(-1 + 2, -3 + 1),(2 - 3, 2 + 2),(1 - 1, -3 + 3)]`

= `[(1, -2),(-1, 4),(0, 0)]`  ...(ii)

From (i) and (ii), we get

(A + BT)T = AT + B

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Balbharati Mathematics and Statistics 1 (Arts and Science) 11th Standard Maharashtra State Board
Chapter 4 Determinants and Matrices
Exercise 4.7 | Q 10 | Page 98
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×